Meryl Tankard : Two feet - Lansac, Regis 1947-; Meryl Tankard Company; Melbourne Festival ([Place of publication not identified] : Meryl Tankard Company, 1988)
Poster promoting a performance at the National Theatre, St Kilda. Features a black and white photograph of Meryl Tankard as Olga. "Presented by the Meryl Tankard Company in conjunction with Melbourne International Festival of the Arts" Sponsors appear at the foot.
Caption title.
Also available online
"Meryl Tankard took over the role of artistic director of the Canberra based Human Veins Dance Theatre in 1989. Tankard changed the name to Meryl Tankard Company. Tankard left Canberra in late 1992"-- Libraries Australia, viewed 1 September, 2016.
Keywords: Tankard, Meryl, -- 1955- -- Posters; Meryl Tankard Company -- Performances -- Posters; Dance companies -- Australian Capital Territory -- Posters; Dancers -- Australia -- Posters; Modern Dance -- Australia -- Posters; Posters, Australian; Australia -- Posters; Australian